Tinnitus psychopharmacology: A comprehensive review of its pathomechanisms and management - Michele Fornaro (Dove Medical Press, 2010)
Michele Fornaro, Matteo MartinoDepartment of Neuroscience, Section of Psychiatry, University of Genova, Genova, ItalyBackground: Subjective tinnitus is a frequent, impairing condition, which may also cause neurotransmitter imbalance at the cochlea. Psychopharmacologic agents, although not being the first-line treatment for tinnitus, may modulate cochlear neurotransmission, thereby influencing the subjective tinnitus experience.Method: A comprehensive review of MEDLINE literature (from January 1990–January 2010) was performed searching for: “tinnitus”, major classes of psychopharmacological agents, and psychiatric disorders. The most relevant clinical evidence is reported briefly along with a concise description of the main neurotransmitters purported to be involved in tinnitus, in order to provide the reader with a rational evaluation of tinnitus therapy with psychopharmacological agents. Results: Although strong methodological issues limit the reliability of the current results, a broad number of psychopharmacological agents have already been considered for tinnitus, both as candidate triggers or potential therapies.Conclusions: Selected psychopharmacological drugs may play a role in the clinical management of this disorder. While the rational use of these agents for the treatment of tinnitus should not be overlooked, research should be undertaken on their neuromodulating actions at the cochlea. Keywords: tinnitus, psychopharmacology, cochlea